Automatic Recloser System of Transformer Using PLC and Scada - Payal S Borade; Vidya S Rajguru; Sonakshi P Sarode; Riya D Dhage; R R Raskar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This project proposes an automatic recloser system for transformers using Programmable Logic Controllers (PLC) and Supervisory Control and Data Acquisition (SCADA) systems. The proposed system aims to improve the reliability and efficiency of power distribution systems by automatically detecting and responding to transformer faults. The PLC monitors the transformer’s condition and sends signals to the SCADA system, which then displays the status and sends alerts to operators. In a fault, the system automatically isolates the faulty transformer and switches to a backup transformer, minimizing power outages and reducing downtime. The proposed system is tested and validated using simulation studies, demonstrating its effectiveness in improving power system reliability.